The Relationship of Perioperative Blood Transfusion With Bladder Cancer Mortality In Radical Cystectomy Patients - Aria Utama Nur Qohari; Ahmad Zulfan Hendri (Indonesian Journal of Cancer, 2020)
Background: Perioperative blood transfusion is correlated to adverse effects which lead to mortality on a few cases of patients with malignancy, especially kidney tumors. The objective of this study is to evaluate the relationship between blood transfusion timings and survival of patients with bladder cancer who undergo radical cystectomy and measure the differences in the outcomes between patients undergoing intraoperative blood transfusion and patients undergoing blood transfusion after surgery.Methods: This research is a retrospective analytic study with a cohort design. Thirty patients with bladder tumors who performed radical cystectomy and did not undergo perioperativechemotherapy were included in the study data. Recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS) were analyzed by the Kaplan-Meier method and compared between groups with log-rank tests. Chi-square test was used for comparative evaluation of each group. Univariate and multivariate analyzes were performed to evaluate the relationship between clinical and pathological variables with risks such as RFS, CSS, and OS. P<.005 were considered statistically significant, and SPSS software was used for the entire analysis process.Results: From a total of 29 patients who had a radical cystectomy, 22 patients received perioperative blood transfusion. The 17 patients had the transfusion intraoperatively while the rest had the transfusion after the operation. The mean of blood loss was 1491 cc and the mean of survival was 13.2 months. Intraoperative blood transfusion was associated with a significantly increased risk of disease recurrence (HR: 1.32; P=.034), bladder cancer mortality (HR: 1.65; P=.015), and all-cause mortality (HR: 12.38; P=.013).Conclusions: Intraoperative blood transfusion is significantly associated with an increased risk of cancer mortality. Further investigation is needed to determine the biological mechanismsunderlying patient outcomes.